Improving Understanding of Ablution Procedures Through The Demonstration Method at State Elementary School 056020 Pematang Rambai - Ferawati, Dian; Hawa, Siti; Ariani, Fatimah; Rahimi; Nurhefti (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to improve students' understanding of the correct ablution procedures through the demonstration method at SD Negeri 056020 Pematang Rambai, Tanjung Pura in the 2023/2024 school year. The demonstration method was chosen because it can provide a more concrete and interactive learning experience, so that students can more easily understand and remember each stage of ablution according to the correct guidance. This study uses a classroom action approach (CAR) which is carried out in two cycles, with each cycle involving planning, implementation, observation, and reflection. The subjects of the study were fourth grade students who had difficulty in understanding and practicing ablution correctly. Data were collected through observation, interviews, and evaluation tests before and after the action. The results showed that the demonstration method significantly improved students' understanding of ablution procedures, as indicated by an increase in the average test score from the first cycle to the second cycle. In addition, this method also increases student activity and involvement in the learning process. Thus, the demonstration method can be used as an effective learning strategy in improving students' understanding of ablution procedures in elementary schools.